Nicotinamidase modulation of NAD(+) biosynthesis and nicotinamide levels separately affect reproductive development and cell survival in C. elegans - Vrablik, Tracy L. (Company of Biologists, 2009)
Nicotinamide adenine dinucleotide (NAD(+)) is a central molecule in cellular metabolism and an obligate co-substrate for NAD(+)-consuming enzymes, which regulate key biological processes such as longevity and stress responses. Although NAD(+) biosynthesis has been intensely studied, little analysis has been done in developmental models. We have uncovered novel developmental roles for a nicotinamidase (PNC), the first enzyme in the NAD(+) salvage pathway of invertebrates. Mutations in the Caenorhabditis elegans nicotinamidase PNC-1 cause developmental and functional defects in the reproductive system; the development of the gonad is delayed, four uterine cells die by necrosis and the mutant animals are egg-laying defective. The temporal delay in gonad development results from depletion of the salvage pathway product NAD(+), whereas the uv1 cell necrosis and egg-laying defects result from accumulation of the substrate nicotinamide. Thus, regulation of both substrate and product level is key to the biological activity of PNC-1. We also find that diet probably affects the levels of these metabolites, as it affects phenotypes. Finally, we identified a secreted isoform of PNC-1 and confirmed its extracellular localization and functional activity in vivo. We demonstrate that nicotinamide phosphoribosyltransferase (Nampt), the equivalent enzyme in nicotinamide recycling to NAD(+) in vertebrates, can functionally substitute for PNC-1. As Nampt is also secreted, we postulate an evolutionarily conserved extracellular role for NAD(+) biosynthetic enzymes during development and physiology.